Inquiry‐based mobile learning in secondary school science education: A systematic review. (28th October 2020) - Liu, Caihua; Zowghi, Didar; Kearney, Matthew; Bano, Muneera
Abstract: Recent years have seen a growing call for inquiry‐based learning in science education, and mobile technologies are perceived as increasingly valuable tools to support this approach. However, there is a lack of understanding of mobile technology‐supported inquiry‐based learning (mIBL) in secondary science education. More evidence‐based, nuanced insights are needed into how using mobile technologies might facilitate students' engagement with various levels of inquiry and enhance their science learning. We, therefore, conducted a robust systematic literature review (SLR) of the research articles on mIBL in secondary school science education that have been published from 2000 to 2019. We reviewed and analysed 31 empirical studies (34 articles) to explore the types of mIBL, and the benefits and constraints of mIBL in secondary school science education. The findings of this SLR suggest new research areas for further exploration and provide implications for science teachers' selection, use and design of mIBL approaches in their teaching. Lay Description: What is already known about this topic?: Inquiry‐based learning (IBL) in science education is a pedagogical approach in which students' learning is driven by an investigative question. The use of mobile technologies can create customized learning opportunities for science students. Mobile technology‐supported IBL (mIBL) can enable seamless science learning experiences. What this paper adds?: Presents a systematic review of empirical studies of mIBL in secondary school science education published from 2000 to 2019; Describes the fundamental research foci, settings and contexts of mIBL studies; Develops a synthesis of 31 empirical studies leading to a categorization of types of mIBL; and Presents the benefits and constraints of mIBL in science education. Implications for practice and/or policy: Provide opportunities for science teachers to rethink the use of different types of mIBL; Learn how to organize activities for implementing various types of mIBL; Inform developers and policymakers about ways of using mobile technologies to support IBL; Outline future research developments of mIBL in secondary science education.